Making A Multi Purpose Liquid (Eco-Enzyme) as An Alternative for Processing Household Organic Waste and Reviewing Its Benefits - Daffa Ulwan Nafilah; Fera Rahmawati; Mohamad Tafrikan; Nur Khasanah (Jurnal Pengabdian KOLABORATIF, 2024)
This activity was conducted to increase public awareness and knowledge in managing household organic waste into eco-enzymes. Eco-enzyme is a natural liquid from the fermentation process of organic kitchen waste such as fruit and vegetable peels, granulated sugar (white sugar, brown sugar, or cane sugar), and water. The training activity was held at the home of the head of Gentan Hamlet, Doplang Village, Bawen Subdistrict, Semarang Regency on Wednesday, October 25, 2023, with the training participants being women members of Dasawisma (Dawis). The activity was carried out using socialization and demonstration methods to facilitate participants' understanding of the material and the process of making eco-enzymes. Based on the evaluation results, the participants were very enthusiastic about learning new knowledge they did not know before. Participants learned about the technology of making eco-enzymes from household waste. In addition to creating a clean environment, the resulting eco-enzyme also provides various benefits for life.